Giant primary melanoma of the skin arising on the left foot - Vladimír Bartoš; Zuzana Štofová (Our Dermatology Online, 2016)
Melanoma of the skin usually does not reach a greater dimension. The authors describe unique case of the patient with a huge (giant) primary cutaneous melanoma. 56-year-old man was diagnosed to have melanoma arising on the left foot. Partial surgical amputation with a complete tumor removal was done. Melanoma measured 8 × 4 cm and exhibited massive ulceration, Breslow's thickness 15 mm, Clark's level V, high mitotic and proliferative activity. A patient was classified as stage III B. After surgery, he was relegated to the oncological dispensary health care and took part additional clinical investigations. Finally, PET/CT scan revealed pulmonary and regional lymph node metastases. Therefore, paliative chemotherapy was started. Huge skin melanomas like this are very rarely diagnosed in clinical practice and they are almost always the result of long-term neglect of growing lesion. Currently, it is not answered, whether certain specific factors predispose some melanomas to grow such enormously